Supercontinuum accumulation along a single femtosecond filament in fused silica. (17th February 2016) - Zhang, Lanzhi; Xi, Tingting; Hao, Zuoqiang; Lin, Jinquan
Abstract: The spectral evolution of a filament formed by femtosecond laser pulses in fused silica is experimentally investigated. It is found that the evolution of the supercontinuum (SC) spectrum along the single filament is closely related with its intensity and length. The energy conversion efficiency of fundamental laser pulse to SC generation increases monotonically with different rates as the filament length increases, showing an accumulating effect along the filament. The results also show that the short-wavelength cutoff of the SC spectra is more sensitive to the intensity of the filament than the conversion efficiency of the SC, which is contributed mainly by the efficiently ionized zone of the filament.